Teoremas de James sobre a não-distorção de normas em espaços de Banach e aplicações. - Motta, Cristina Boaz da (2019)
This dissertation aims to show that isomorphic copies of c0 and l1 in Banach spaces are undistorted. In other words, they generate quasi-isometric copies of these spaces. In approaching the main theme of this dissertation, we will take as theoretical base the scientific works of several authors, especially James (1964). The Functional Analysis area provides primary tools for solving various problems in both Banach space theory and various areas of knowledge. Hence the importance of this work.